2018
DOI: 10.1038/s41416-018-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Derazantinib (ARQ 087) in advanced or inoperable FGFR2 gene fusion-positive intrahepatic cholangiocarcinoma

Abstract: BackgroundNext-generation sequencing has identified actionable genetic aberrations in intrahepatic cholangiocarcinomas (iCCA), including the fibroblast growth factor receptor 2 (FGFR2) fusions. Derazantinib (ARQ 087), an orally bioavailable, multi-kinase inhibitor with potent pan-FGFR activity, has shown preliminary therapeutic activity against FGFR2 fusion-positive iCCA.MethodsThis multicentre, phase 1/2, open-label study enrolled adult patients with unresectable iCCA with FGFR2 fusion, who progressed, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(243 citation statements)
references
References 40 publications
(43 reference statements)
5
213
0
8
Order By: Relevance
“…The efficacy seen across several early-phase clinical trials of FGFR2 inhibitors in patients with advanced refractory ICC (14,(28)(29)(30) represents a breakthrough in a disease with no FDA-approved targeted therapies to date. However, as seen with other tyrosine kinase inhibitors, the rapid emergence of resistance associated with recurrent acquired mutations in the target's kinase domain has limited the durability of benefit to ATP-competitive inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy seen across several early-phase clinical trials of FGFR2 inhibitors in patients with advanced refractory ICC (14,(28)(29)(30) represents a breakthrough in a disease with no FDA-approved targeted therapies to date. However, as seen with other tyrosine kinase inhibitors, the rapid emergence of resistance associated with recurrent acquired mutations in the target's kinase domain has limited the durability of benefit to ATP-competitive inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, phase I-II clinical trial open-label study enrolled adult patients with unresectable iCCA with FGFR2 fusion, who progressed, were intolerant or not eligible to first-line chemotherapy. Overall response rate was 20.7%, and disease control rate was 82.8% [51]. As for the other FGFR inhibitors, the treatment was well tolerated with a manageable safety profile.…”
Section: Derazantinibmentioning
confidence: 90%
“…For this purpose, genetic analyses of liver tissues from patients with HCC for genomic medicine have provided important information about tumor initiation, progression, and chemosensitivity [168]. The findings from these studies can be used to develop personalized gene-based therapy and genome-based diagnosis in the tumor; therefore, various clinical trials to determine the disease activity and sensitivity to the specific therapy are ongoing [169][170][171][172][173]. One of the trials bridged into the phase 1/2 trial is NCT03480152, examining the effect of mRNA cancer vaccine, delivering mRNA containing epitopes from immunogenic neoantigens, predicted neoantigens, and mutations in tumor suppressor or driver genes, by intramuscular injection [159][160][161].…”
Section: Ongoing Clinical Trials For Gene-based Diagnosismentioning
confidence: 99%
“…This study aimed to find the genes that are expressed in both the circulating white blood cells and the liver of patients, using differential gene expression analysis, with varying degrees of liver damage of different causes with or without liver cancers. These studies include a microarray analysis of gene expression patterns in liver tumors to determine new tumor and treatment markers (NCT00373737); screening of the methylation phenotype of liver cancer to predict the prognosis (NCT01786980); analysis of different gene expression patterns in liver cancer and the blood to determine genes that are expressed in both circulating white blood cells and the liver of patients with varying degrees of liver damage of different causes (NCT00160940); a genotype-guided dosing analysis of mFOLFIRINOX for primary and metastatic liver cancers (NCT01643499); phase II molecular analysis to assess how well the treatment, directed by genetic testing, works in patients with solid tumors or lymphomas that have progressed following at least one line of standard treatment, or for which no agreed treatment approach exists (NCT02465060); an analysis of the molecular mechanism of sorafenib resistance in HCC patients assessed by gene expression profiles (NCT02733809) [169]; a phase I/II study to determine fibroblast growth factor receptor (FGFR) genetic alterations treated with novel FGFR inhibitor (ARQ-087) (NCT01752920) [170]; a phase I study to determine genetic alteration of the proto-oncogene MET in patients with solid tumors, including liver cancer treated with a novel MET/CSF1R/SRC inhibitor, TPX-0022 (NCT03993873); an investigation of vascular endothelial growth factor receptor (VEGFR), promoting cell growth and metastasis in HCC (NCT01892072); an assessment the impact of IL-28B rs12979860 and rs4803217 gene polymorphisms on hepatitis C virus (HCV)-related HCC (NCT02507882) [171]; analyses of the expression of a specific set of genes and of tumor antigens in cancer tissue from patients with HCC (NCT00858000); an assessment of matrix metalloproteinase-1 genotype polymorphism as a risk factor for HCV-related HCC (NCT03722628) [172]; determination of the role of circulating tumor cells as biomarkers of prognosis and predictors of efficacy of drug therapy for patients with HCC (NCT01930383); and a phase II study comparing the efficacy and safety of SOR versus infusional 5-fluorouracil in HCC based on the information of pERK concentration, phospho VEGFR concentration, plasma proteomics, and gene expression (NCT00619541) [173] (Table 3). While the detailed information is available for 14 studies, only a few results have been reported to date and the remainder of the study is mostly under assessment ( Table 3).…”
Section: Nct00373737 Microarray Analysis Of Gene Expression In Livermentioning
confidence: 99%
See 1 more Smart Citation